CAPSAICIN EXTRACTION FROM HOT PEPPERS - A.Sh.Ziyadullayev; G.B.Hamrokulov; F.T.Norgitov; A.B.Khusenov (Journals Park Publishing, 2023)
The article studied the extraction process from hot pepper crop to develop a method for the analysis of capsaicin. Effects of extractant, hydromodulus and particle sire on carsaicin extraction rate and frequency were studied.
Keywords: Capsaicin, hot pepper, extraction, extractant, hydromodulus.